DRTP: A Disruption Resilient Hop-by-Hop Transport Protocol for Synchrophasors Measurement in Electric Transmission Grids - Boyang Zhou; Chunming Wu; Qiang Yang; Xiang Chen (IEEE Access, 2022)
In a modern electric power transmission grid, the phasor measurement unit requires a reliable transport of its sampled statistics with a low end-to-end failure rate (EEFR) to ensure the accuracy of the grid state estimation. However, EEFR can be deteriorated by packet losses due to multiple link disruptions in the primary forwarding path (PP). To address that, we investigate a novel disruption resilient transport protocol (DRTP) enabling hop-by-hop retransmission utilizing the redundant subpaths (RSPs) available for the PP to increase reliability. It addresses the new distributed collaboration issue under multiple link failures to avoid cache mismatching. These have not been considered by the existing approaches. The DRTP was evaluated in the ndnSIM simulator through both the typical and general routes that are constructed from real transmission grids. The numerical results demonstrate that it has a significant advantage in reducing the EEFR with a low end-to-end delivery time under serious link disruptions.